2020
DOI: 10.1186/s40816-020-00211-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydro-methanol stem bark extract of Burkea africana on erythrocyte osmotic fragility and haematological parameters in acetaminophen-poisoned rats

Abstract: Background Burkea africana is a widely used medicinal plant in folkloric medicine in many developing countries of the world. It is useful in the treatment of various ailments including hepatitis, jaundice, diarrhea, stomach aches, abscesses, oedema, epilepsy, bloody diarrhea, gonorrhea, syphilis, toothaches and poisoning. Nevertheless, there are little or no scientific evidence to substantiate this medicinal claim by traditional healers. Burkea africana stem bark was therefore, investigated for its protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Osmotic fragility curve for the rat erythrocytes exposed to different doses of Dissotis rotudifolia extract is presented in figure 1. The haemolysis pattern of rat erythrocyte suspended in increasing concentration of saline conforms to published report by Chikezie and Uwakwe, [5], Saad and Habib, [6], Swem et al, [7] and Duchnowicz et al, [20]. Osmotic fragility is affected by certain factors including the chemical composition of the membrane and its viscoelasticity [21].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Osmotic fragility curve for the rat erythrocytes exposed to different doses of Dissotis rotudifolia extract is presented in figure 1. The haemolysis pattern of rat erythrocyte suspended in increasing concentration of saline conforms to published report by Chikezie and Uwakwe, [5], Saad and Habib, [6], Swem et al, [7] and Duchnowicz et al, [20]. Osmotic fragility is affected by certain factors including the chemical composition of the membrane and its viscoelasticity [21].…”
Section: Resultssupporting
confidence: 86%
“…Erythrocyte fragility is affected by the composition and integrity of the membrane, and the cell surface-area to volume ratio [2]. Drugs [3,4] and medicinal plants [5,6,7,8] have been reported as some of the external factors that can influence erythrocyte osmotic fragility [9].…”
Section: Introductionmentioning
confidence: 99%
“…In a different study, the authors reported that a hydromethanol extract of B. africana stem bark preserved erythrocyte integrity and displayed hematopoietic effects, and this may support the absence of significant hemolytic effect of B. africana extract in this study. 30 Besides, an ethanol extract of the plant showed a non-cytotoxic effect on normal cells and a non-cancerous cell line but was preferentially cytotoxic to a cancerous cervical cell line. 31 This renders the extract as a potential antiplasmodial agent that will not exert deleterious effects on host erythrocytes and other body cells.…”
Section: Discussionmentioning
confidence: 98%
“…The osmotic fragility test enables the diagnosis of erythrocyte abnormalities in several diseases, including autoimmune hemolytic anemia, thalassemia, and hereditary spherocytosis . A preliminary evaluation of the safety profile of drugs and the discovery of hidden pathologies requires such analysis . The erythrocyte fragility test is a concentration analysis method.…”
Section: Discussionmentioning
confidence: 99%